Environmental and health impacts of contaminants of emerging concerns: Recent treatment challenges and approaches - Yadav, Deepak; Rangabhashiyam, S.; Verma, Pramit; Singh, Pardeep; Devi, Pooja; Kumar, Pradeep; Hussain, Chaudhery Mustansar; Gaurav, Gajendra Kumar; Kumar, Kuppusamy Sathish (Chemosphere (Oxford), 2021)
In the past few decades, new contaminants of emerging concern (CECs) in the air, water, and soil have gained significant attention due to their adverse impact on human health and the environment. The sources of CECs have been identified in different forms from domestic and industrial activities such as personal care products and pharmaceuticals. It has been established that aqueous medium plays a major role in the dissemination of various contaminants, like drinking water, reservoirs, lakes, rivers and waste with water medium. There remains inadequate technology for the treatment of CECs in the wastewater systems. Though different techniques have advanced for the treatment of CECs, they still pose a severe threat to human health and disturb the ecological balance. In this review, the characteristics, recent technologies, risk assessment and management of CECs have been discussed. The primary aim is to highlight the new innovative and cost-effective technologies for the remediations of CECs in all forms. Biochar is readily and economically available in abundance and an economical adsorbent with 100% adsorptive removal for H2PO4−. The bibliometric analysis also performed to understand the emerging research trends on the treatment techniques, which can help in developing a guiding pathway to modern research in academia and industry. •CECs pretence a threat to human health as well as the ecological balance.•Innovative and cost-effective technologies to treat CECs are deliberated.•Deliver acumens on risk assessment and management of CECs.•Multipronged, flexible risk valuation and response strategy essentials to advance.•Solar photocatalysis using TiO2 one of the prospective approaches for handling pharmaceuticals CECs.